WORD FORMATION PROCESSES OF THE TERMS USED BY CLOTHES ONLINE SHOPS IN BLACKBERRY MESSENGER - RAHAYU, PUJI (Jurnal Ilmiah Mahasiswa FIB, 2014)
As the language develops every time, there are  new languages  and terms emerge day by day in  the society. A new language and term use new words that we can relate to the one of linguistics branches of the morphological aspect namely word formation process.  Word formation process is the process of creating new word and terms from the use of old words. One of the language phenomenon is in the practice of  language  used in  online shop business specifically clothes online shops  sold in Blackberry Messenger  in Blackberry Smartphone. Clothes online shop  is  a  popular shopping  way  nowadays  because  it  offers the practical way of shopping  for the buyers.  People as the consumer  prefer  to buy  their clothes  practically  by using Internet  in clothes online shops  rather than  going to  the  clothes  shops  such as boutiques, mall, department store,  or  traditional market. Clothes  online shop is the clothes shop which sells many clothes of man, woman and also children by uploading their pictures via Internet as the main marketing tool. It is sold via websites or social media  such as  Twitter,  Facebook,  Instagram,  Blackberry  Messenger, and many others.  In this case,  the writer observed  the  clothes  online  shops which are  sold  in Blackberry Messenger  through the group conversation  and clothes information in clothes online shops. This research is aimed at finding out; (1). The list of  the terms used in clothes online shops,  also (2).  The word  formation processes of the terms used by clothes online shops. Keywords: Word Formation Process, Term, Clothes Online Shop, Blackberry, Blackberry  Messenger, BBM.